Upon a spring breeze [large type] - Irvin, Kelly (Irvin, Kelly. Every Amish season novel., 2017)
Bess Weaver, twenty and expecting her first child, is making stew for her beloved mann, Caleb, one minute, and the next she's burying him after a tragic accident. Facing life as young widow, Bess finds comfort only in tending the garden at an Englisch-owned bed and breakfast. Aidan tries to repress his guilt over his best friend Caleb's death and his long-standing feelings for Bess by working harder than ever. But as he spends time with young son Caleb left behind, Aidan seems to be growing closer to the boy's beautiful mother.